Condiciones académicas y su relación en la formación profesional de los estudiantes de la escuela de Ingeniería en Gestión Ambiental – 2021 - Valles Mori, Russel Gustavo (2025)
The work was developed in the environments of the local A-10 where the classes of the Professional Training School of Environmental Management Engineering are developed, located between the populated centers of Zungarococha and Puerto Almendra, the purpose was to determine the influence of academic training in the professional profile of said school, the work was non-manipulative, observational Ex Post Facto, the universe was made up of 60 students 5th level (9th and 10th cycle), chosen at random, the technique used was the interview and the application of a survey with structured questions, reaching the conclusion: Regarding the Teaching learning Process (63.3% claim to not know much about the subject, they only dictate their classes 50% say so and 43.3% use educational materials); the institutional climate is regular (38.3% say so) and the teacher-student treatment is Authoritarian (70%); only (20%) know the Study Plan and (80%) do not know it; Graduates have few job options (60% agree), there are more job opportunities outside the city (63.3%), and in obtaining their degree (100%) agree that they must develop a research project and present it before a judging panel.